Rancang Bangun Sistem Informasi Inventaris Barang di Gudang Berbasis Web Pada PT.XYZ - Ilham Banuaji; Nizirwan Anwar; Binastya Anggara Sekti; Agung Mulyo Widodo (Ikatan Ahli Informatika Indonesia, 2023)
PT. XYZ is a company engaged in the field of trading in goods, whose main activity is recording stock in and out of goods in warehouses, currently still using Microsoft Excel. Along with the development of the company, activity and the number of transactions also continues to increase, recording using Microsoft Excel is felt lacking because of frequent delays and othererrors or human errors. Another problem is regarding the inaccurate warehouse design, which makes it difficult to find goods. The purpose of this research is to overcome the problems that arise and expedite the process of recording data on goods entering or leaving the warehouse, searching for goods, making final reports, archiving, and data backup. In this study, the authors will use the prototype method which has three stages, namely Listen to Customer, Build and Revise Mockup, and Customer Test Drives mock-up. The results of this study are able to overcome the problems that occur in recording with Microsoft Excel and warehouse design. Utilization of a web-based inventory information system with this database is proven to be able to provide solutions to problems in inventory. It can be used as an integrated system for collecting, storing, searching for goods, and processing data, as well as reporting.